Minerals and Lipids Profiles in Cardiovascular Disorders in South Asia Cu, Mg, Se, Zn and Lipid Serum Profiles for the Example of Patients in Pakistan - Rizvi, Nayab Batool; Nagra, Saeed Ahmad (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book correlates different minerals and lipids serum profiles with the prevalence of cardiovascular disorders in South Asian countries with special emphasis on Pakistan. Cardiovascular disorders (CVD, e.g. coronary heart diseases, hypertension, rheumatic heart disease, angina, heart failure and deep vein thrombosis) show significantly increasing rates in South Asian countries like Pakistan and have become a major health problem. Nevertheless, the data on any aspect of cardiovascular problems still is scanty. The serum profiles of different minerals (copper, magnesium, zinc, selenium) and lipids are analyzed in detail. The presented data will thus lead to a better understanding of the problem and help to provide possible solutions, which can be achieved, e.g. through ameliorated minerals profiles in the daily diet. These results can help develop better dietary management strategies in the prevention and treatment of CVD.